Analisa Kinerja Metode Support Vector Machine untuk Analisa Sentimen Ulasan Pengguna Google Maps - Andharini Dwi Cahyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sentiment Analysis is a subset of data mining that analyzes, understands, processes, and extracts textual data in the form of opinions or reviews about a certain object. The advancement of technology, such as Google Maps, can make it easier to find information on the location of an object. Google Maps also gives an object review. These reviews provide information that can be used to examine the feelings expressed by visitors. A text mining methodology with the Support Vector Machine method is utilized to process customer review text data. This method is part of a classification strategy that recognizes and categorizes data into two portions separated by a hyperplane. The data used in this case study are visitors' reviews that is recorded on Google Maps Review of the Eternal Flame, a tourist attraction obejct located in Sumenep.